Math 60 Proficiency Practice1
- -14 + (-9) =
- (-5)(2)(-1)(2) =
- -5 + 2 + (-1) + (-2) =
- -20 – 16 =
- 6 – (-6) =
- –(-4) – 1 =
- 7 – 10 – 1 – (-3) =
- -4 + 9(-2) =
- Evaluate the expression
- Evaluate the expression
1.) -23 / 2.) 20 / 3.) - 6 / 4.) 6 / 5.) - 36 / 6.) 12
7.) 3 / 8.) - 1 / 9.) - 22 / 10.) - 24 / 11.) 1 / 12.) - 18
M60 Proficiency Practice 2
- (-11) + 17 + (-5) =
- -5 – (-4) – 3 =
- Evaluate 2xy – y when x = -3 and y = 2.
- Simplify by combining like terms: 6 – 3x – 10 – 4x.
- Simplify: -4x + 10 – 3x – 2
- Solve: (Show all steps): 10. Solve: (Show all steps):
9x + 4 = 22 -3x + 12 = -3
1.) 1 / 2.) - 4 / 3.) 4 / 4.) 0 / 5.) 206.) - 14 / 7.) -7x – 4 / 8.) -7x + 8 / 9.) x = 2 / 10.) x = 5
M60 Practice for Proficiency 3
1. (-14) + (-8) + 21=
2. 20 – 7 – (-10) =
3.
4.
5.
6. Evaluate wp + 5w when w = 4 and p = -3.
7. Simplify by combining like terms: 4 + 2x – 10 – 3x
8. Simplify: -4x + 3 – 6 – 2x
9. Solve: (Show all steps)10. Solve: (Show all steps)
5 x – 8 = 122x + 3 = -5
1.) - 1 / 2.) 23 / 3.) - 13 / 4.) 3 / 5.) 166.) 8 / 7.) - x - 6 / 8.) - 6x - 3 / 9.) x = 4 / 10.) x = - 4
M60 Practice for Proficiency4
1. 17 + (-20) + 5 =
2. -12 – 6 – (-20) =
3.
4.
5.
6. Evaluate 3xz – 4z when x = -2 and z = 5
7. Simplify by combining like terms: -6 + 2p – 4 + 5p
8. Simplify: 6x2 – 24x – 8x2 + 3x
9. Solve: (Show all steps)10. Solve: (Show all steps)
4x + 3 = 193x – 8 = -20
1.) 2 / 2.) 2 / 3.) - 10 / 4.) 10 / 5.) - 786.) - 50 / 7.) 7p - 10 / 8.) -2 x2 – 21 x / 9.) x = 4 / 10.) x = - 4
M60 Practice for Proficiency5
1. (-3) + 12 + (-14) =
2. 8 – (-4) – 13 =
3.
4.
5.
6. Evaluate 4x + xp when x = -3 and p = -4
7. Simplify by combining like terms: 12x2 – 7x3 + 3x3 – 8x2
8. Simplify: -2x + 10 + 2x – 5
9. Solve: (Show all steps)10. Solve: (Show all steps)
4x – 5 = -17- 8x – 2 = 54
1.) - 5 / 2.) - 1 / 3.) - 8 / 4.) 4 / 5.) - 126.) 0 / 7.) 4 x2 – 4 x3 / 8.) 5 / 9.) x = - 3 / 10.) x = - 7
M60 Practice for the Proficiency6
1. 14 + (-20) + (-2) =
2. -4 – 8 – (-6) =
3.
4.
5.
6. Evaluate 2x + xy when x = -3 a and y = - 2
7. Simplify by combining like terms: -4y + 7y2 – 8y – y2
8. Simplify: 3x – 4 –(-3x) – 5
9. Solve: (Show all steps)10. Solve: (Show all steps)
3x + 2 = 11- 4x – 7 = -11
1.) - 8 / 2.) - 6 / 3.) - 38 / 4.) 2 / 5.) - 166.) 0 / 7.) - 12 y + 6y2 / 8.) 6 x - 9 / 9.) x = 3 / 10.) x = 1